PRODUKTIVITAS KAMBING BOERAWA PADA PEMELIHARAAN PEDESAAN DENGAN PEMANFAATAN KONSENTRAT BERBASIS LIMBAH AGROINDUSTRI DI PROVINSI LAMPUNG - , KUSUMOA ADHIANTO; , Prof. Dr. Ir. Nono Ngadiyono, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research objective is to find out the 1) profile identification of Boerawa goat farmer groups in Gisting sub district, 2) Data on Boerawa Goat Productivity In Rural Maintenance in District Gisting, and 3) performance improvement of Boerawa goat reproduction and production in rural raising setting by giving feeding concentrate based on agro industrial waste. The first research uses survey method to obtain primary and secondary data. Respondents are goat farmers or farmer who has Boerawa cattle as a source of income. The second research is conducted in the field to identify 60 first pregnant Boerawa goats